REGULASI HUKUM TERHADAP INFLUENCER MARKETING: "ETIKA DAN TANGGUNG JAWAB DALAM IKLAN DIGITAL" - Oktariani, Masjida; Nayla Ramadhanty, Dwi; Laini Putri, Keisya; Handayani, Sri (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This research aims to determine the existence of legal regulations governing the ethics and responsibilities of influencer marketing in conducting digital advertising. The research method used is Normative Juridical, the approach is based on the main legal material by examining theories, laws and regulations related to research. Based on existing legal regulations, it is emphasized that an influencer must have ethics and responsibility in carrying out digital advertising. This is important to do to create a digital advertising environment that is more transparent, fair and responsible.